PERTUMBUHAN AKUN INSTAGRAM PERPUSTAKAAN PTKIN DI INDONESIA - Fiqru Mafar (Al'Adalah, 2020)
Instagram is one of the most popular social media in society. Seeing this potential, some university library managers have started to look at Instagram as well as promoting the institutions that they manage. The object of this research is to investigate the existence of the PTKIN library on Instagram. The method in this study uses a library model by analyzing the start date of posting, the average posting, and the number of followers on each of the PTKIN library Instagram accounts in Indonesia. The results showed that in general, the existence of PTKIN Library on Instagram was high. It can be seen that there are 37 Instagram accounts from 58 PTKIN libraries in Indonesia. In other words, more than half or 63,79% of PTKIN libraries in Indonesia have used Instagram to promote the institutions they manage.